2021
DOI: 10.1111/myc.13382
|View full text |Cite
|
Sign up to set email alerts
|

The use of combined PCR, fluorescence in situ hybridisation and immunohistochemical staining to diagnose mucormycosis from formalin‐fixed paraffin‐embedded tissues

Abstract: Objective: To develop a comprehensive diagnostic system for mucormycosis from formalin-fixed paraffin-embedded tissues, consisting of own-designed real-time polymerase chain reaction (PCR) assays, fluorescence in situ hybridisation, and immunohistochemical staining. Methods: We designed 11 primers and probes for specific real-time PCR assays based on genome sequences, and validated the specificity by Aspergillus, Fusarium, Scedosporium, Lomentospora, Cryptococcus and Candida species. Formalin-fixed paraffin-em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Although mucorales PCR has not yet been included in these standards due to the lack of standardization or test availability, it has significantly improved mucormycosis diagnosis in recent years. Fluorescence in situ hybridization methods for promptly identifying Mucorales from formalin-fixed, paraffin-embedded tissues, along with real-time quantitative PCR systems for precise genus- and species-level identification, have been developed to accurately detect pathogenic Mucorales in tissues ( 12 ). A French study, conducted at multiple centers, assessed the usefulness of qPCR in diagnosing invasive trichothecosis through serum samples.…”
Section: Discussionmentioning
confidence: 99%
“…Although mucorales PCR has not yet been included in these standards due to the lack of standardization or test availability, it has significantly improved mucormycosis diagnosis in recent years. Fluorescence in situ hybridization methods for promptly identifying Mucorales from formalin-fixed, paraffin-embedded tissues, along with real-time quantitative PCR systems for precise genus- and species-level identification, have been developed to accurately detect pathogenic Mucorales in tissues ( 12 ). A French study, conducted at multiple centers, assessed the usefulness of qPCR in diagnosing invasive trichothecosis through serum samples.…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis of mucormycosis is difficult given its relatively nonspecific initial symptoms [4] , [5] ; the diagnostic dilemma is compounded by inconsistent staining patterns of Mucormycetes on commonly used fungal stains and the challenges and slow timeline of culturing mucormycosis in the routine lab setting [13] , [18] . If mucormycosis is on the differential diagnosis, nucleic acid based diagnostic modalities offer high sensitivity and specificity with a much faster turn-around time: results can be available within hours of sample collection [18] , [19] . A wide array of samples are suitable for testing, including fresh and frozen tissue, formalin-fixed paraffin-embedded tissue, blood, urine, and bronchoalveolar lavage fluid [18] , [20] .…”
Section: Discussionmentioning
confidence: 99%
“…The combination of various diagnostic methods has emerged as a prominent trend and has proven advantageous in augmenting the diagnostic accuracy for different diseases. For example, previous study has shown that the combination of polymerase chain reaction (PCR), fluorescence in situ hybridization, and immunohistochemical staining can significantly enhance the diagnostic accuracy for mucormycosis ( 33 ). Moreover, PCR in combination with galactomannan (GM) exhibits superior diagnostic performance compared to GM alone in identifying Aspergillus infections ( 34 ).…”
Section: Discussionmentioning
confidence: 99%